2019
DOI: 10.3174/ajnr.a6093
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of MRI in Diagnosing Brain AVM Recurrence after Angiographically Documented Exclusion in Children

Abstract: BACKGROUND AND PURPOSE: MRI is routinely performed following brain AVM after treatment in children. Our aim was to determine the predictive values of contrast-enhanced MR imaging and TOF-MRA for brain AVM recurrence in children, compared with conventional angiography and the role of 3D rotational angiography-MR imaging fusion in these cases. MATERIALS AND METHODS: We included all pediatric patients with brain AVMs during an 18-year period with angiographically documented obliteration after treatment. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Based on suggested follow-up in children [31] and from the adult cases thus far, follow-up for 10 years, with routine imaging at 1 year, 5 years, 10 years and for any new or progressive neurological signs and symptoms, would be reasonable. Although DSA is still the gold standard modality and was utilized to detect recurrence in all reported cases, a 2019 study found that contrast-enhanced magnetic resonance imaging and angiography (MRI/MRA) was suitable for surveillance, with DSA subsequently used for confirmation [32].…”
Section: Discussionmentioning
confidence: 99%
“…Based on suggested follow-up in children [31] and from the adult cases thus far, follow-up for 10 years, with routine imaging at 1 year, 5 years, 10 years and for any new or progressive neurological signs and symptoms, would be reasonable. Although DSA is still the gold standard modality and was utilized to detect recurrence in all reported cases, a 2019 study found that contrast-enhanced magnetic resonance imaging and angiography (MRI/MRA) was suitable for surveillance, with DSA subsequently used for confirmation [32].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the most recently published analysis about the issue of AVM surveillance concludes that MRI as a surveillance imaging modality for that patient population should, at present, be supplemented by conventional angiography. This is based upon the fact that when TOF-MRA and contrast enhanced MRI are collectively used and interpreted together, their complementary predictive value is in the order of 85%, compared with conventional angiography [34].…”
Section: Discussionmentioning
confidence: 99%
“…The secondary outcomes: obliteration rate, subsequent hemorrhage, complication rate, and improvement in clinical symptoms (epilepsy, headache, neurological dysfunction) at 3 years after treatment. The obliteration rate will be evaluated by DSA or MRI, as several previous studies have suggested that MRI could provide a similar assessment of the obliteration rate as DSA [ 18 ]. The subsequent hemorrhage is defined as intracranial hemorrhage that could be attributed to AVM rupture with symptomatic and CT evidence.…”
Section: Methodsmentioning
confidence: 99%